2009
DOI: 10.1016/j.jcmg.2009.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Hyperintense Plaque With Noncontrast T1-Weighted Cardiac Magnetic Resonance Coronary Plaque Imaging

Abstract: The typical HIP case was associated with ultrasound attenuation, positive remodeling, remarkably low computed tomography density, and a high incidence of slow-flow phenomena. Noncontrast T1WI in cardiac magnetic resonance imaging may be useful for the assessment of coronary plaque characterization in patients with coronary artery disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
79
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(88 citation statements)
references
References 29 publications
5
79
1
Order By: Relevance
“…MRI imaging studies have shown that this technique can identify the presence of thrombus and high-risk plaques [114,115]. T1-weighted imaging can also provide useful prognostic information: in a study that included 568 patients with suspected CAD, an increased coronary plaque intensity in T1-weigthed imaging was independent predictor of future adverse cardiovascular events at 55 months follow-up (hazard ratio: 3.96; 95% confidence interval: 1.92-8.17; P < 0.001); nevertheless, there is no data today about the efficacy of MRI in detecting lesions that are likely to progress and cause cardiovascular events [116].…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%
“…MRI imaging studies have shown that this technique can identify the presence of thrombus and high-risk plaques [114,115]. T1-weighted imaging can also provide useful prognostic information: in a study that included 568 patients with suspected CAD, an increased coronary plaque intensity in T1-weigthed imaging was independent predictor of future adverse cardiovascular events at 55 months follow-up (hazard ratio: 3.96; 95% confidence interval: 1.92-8.17; P < 0.001); nevertheless, there is no data today about the efficacy of MRI in detecting lesions that are likely to progress and cause cardiovascular events [116].…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%
“…In addition, noncontrast, TIW CMR was able to directly visualize thrombus in acute myocardial infarction and to detect the presence of coronary high-intensity plaques (HIPs), which correspond to positive remodeling and low-density plaques on CT [76,77]. Noguchi et al [78] took a further step by demonstrating that HIPs identified by non-contrast T1W MRI were significantly associated with coronary events.…”
Section: Coronary Artery Wall Imagingmentioning
confidence: 99%
“…[59][60][61][62][63] HIP was defined as plaque with higher plaque to myocardium signal intensity ratio (PMR), 59) which was calculated as the signal intensity of the cor- …”
Section: Magnetic Resonance Imaging (Mri)mentioning
confidence: 99%